Zakah administration and its importance: a review - Ummulkhayr, Adamu; Owoyemi, Musa Yusuf; Mohamad Cusairi, Rafidah (2016)
Zakah is the economic pillar of Islam.It is the cornerstone of the Islamic economy.It is enjoined by Allah on the wealthy to forfeit a specific amount of their wealth that has reached nisab, for the benefit of the poor.Zakah administration in Islam is carried out by authorities established by the state, or voluntary Muslim organizations, as the case may be. This paper which is a literature review paper focuses on the administration of zakah and its importance in the society.The responsibility of zakah administration as belonging to the state was established, as well as the benefits of its administration by authorities. This paper highlighted the role of nongovernmental organizations in the management of zakah. It discussed the need for Muslims living under non Islamic jurisdiction to take up the challenge of establishing institutions that will be responsible for zakah administration so that Muslims in that jurisdiction can enjoy the benefit of zakah as commanded by Allah.